Development and validation of versatile species-specific primer assays for eDNA monitoring and authentication of 10 commercially important Peruvian marine species - Alan Marín; Ruben Alfaro; Lorenzo E. Reyes-Flores; Claudia Ingar; Luis E. Santos-Rojas; Irina B. Alvarez-Jaque; Karen Rodríguez-Bernales; Cleila Carbajal; Angel Yon-Utrilla; Eliana Zelada-Mázmela (PLoS ONE, 2025)
Molecular identification assays provide crucial support in the research and regulation of aquatic resources. Among them, species-specific primers provide significant discriminatory power for fast and simultaneous differentiation of closely related species. In this study, we developed species-specific primers for environmental DNA (eDNA) monitoring and identification of 10 fish and shellfish species commonly found in the Peruvian seafood sector. To ensure versatility and high specificity, our primers were subjected to various testing methods including PCR, qPCR, and DNA sequencing, supported by robust validation assays. This validation process included a) an in-silico stage using self-generated and public DNA sequences; b) an in-vitro stage using target species sourced from vouchered specimens, as well as fresh and cooked commercial samples, early life stages, and a wide range of non-target species; and c) an in-situ stage using eDNA samples collected from different Peruvian marine ecosystems. Our novel species-specific primers successfully passed the validation process, demonstrating high efficiency and specificity by unequivocally identifying all target species with 100% accuracy and without cross-species reactions. These primers are thus valuable tools for eDNA monitoring, seafood authentication, and combating illegal, unreported, and unregulated fishing. The assays presented in this study can support effective fishery management and conservation efforts not only in the Peruvian fishery sector but also in other countries where our target species are present or imported.